UJI DAYA TERIMA DAN KANDUNGAN GIZI SELAI KULIT BUAH NAGA (Hylocereus polyrhizus) - Astri Handayani Hutauruk; Fitri Ardiani; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Dragon fruit peel (Hylocereus polyrhizus) has been considered only a leftover by the community as it is well-thought-out useless while the dragon fruit peel still contains nutrients that are beneficial to the health such as vitamine C, vitamine E, vitamine A, terpenoid, and flavonoid. It also has greater antioxidant activity than fruit flesh itself. Dragon fruit peel can be untilized into food products, one of which is jam. The purpose of this study is to know the acceptance as well as the nutrition of vitamine C and fiber in dragon fruit peel jam. This study was an experimental study with completely randomized designusing two treatments: Dragon fruit peel 60%: 40% fine sugar and dragon fruit peel 50%: 50% fine sugar. The acceptability of dragon fruit peeljam was conducted on 30 students of the Faculty of Public Health University of Sumatera Utara and nutritional content analysis conducted in the Biochemistry Laboratory FMIPA University of Sumatera Utara. Organoleptic test data were analyzed by T Test - Independent Test. The result analysis of nutrient content of dragon fruit peeljam with A1 treatment(60%:40%) had vitamin C content of 48.4% and fiber 5.4%. The result analysis of nutritious content of dragon fruit peel with A2 treatment (50%: 50%) has vitamin C content of 36.66% and fiber of 4.53%. Based on organoleptic tests on color, aroma, taste and texture, it is known that panelists prefer jam with a ratio of 50% dragon fruit peel and 50% fine sugar. Test T - Independent Test shows the difference of acceptability test from both dragon fruit peeljam crusts in terms of color, smell, taste, and texture indicator. It is suggested that the public be able to utilize the dragon fruit peel to bejam as an additional food alternative as bread stuffing. Further research is needed on the content of other micro substances confined in dragon fruit peel. Keywords: dragon fruit peel, jam, acceptability test, vitamine C, fiber